Nickel supported catalyst for hydrodeoxygenation of bio-oil model compounds / Sharafadeen Gbadamasi - Sharafadeen , Gbadamasi (2016)
The continuous depletion of crude oil reserves and environmental concern has make the search for alternative energy source more imperative. Biomass, which is abundant and carbon neutral energy source has been identified as a potential feedstock for the production of fuel, chemicals and carbon-based materials. Bio-oil, a liquid product of fast pyrolysis of biomass, has gained substantial interest in recent decades with the aim of mitigating and subsequently substituting transport fuel. The combustion of bio-oil produces negligible amount of harmful emissions, such as nitrogen oxides (NOx), sulphur dioxide (SO2) and soot. Additionally, emitted carbon dioxide (CO2) is being recycled into the plant by photosynthesis, hence preventing global warming effect. However, bio-oil possesses undesirable properties such as high polarity, viscosity and acidity, and chemical instability due to its high oxygen and water contents. Consequently, this study investigated the first time application of Ni/Al-SBA-15 catalysts in hydrodeoxygenation of bio-oil model compounds (dibenzofuran and guaiacol). Ni/Al-SBA-15 catalysts with different Si/Al (Si/Al = 50, 60, 70 and 80) mole ratios were synthesized and their catalytic performance was tested for hydrodeoxygenation of dibenzofuran and guaiacol as bio-oil model compounds in a batch reactor. The catalysts were synthesized using the impregnation method and systematically characterized using XRD, N2-adsorption desorption, Raman, H2-TPR, NH3-TPD, XRF, and FESEM techniques. The characterization results reveal that all the synthesized catalysts are mesoporous (pore size range = 3.80–5.20 nm) and possess high surface areas ranging from 665–740 m2/g. Further, the incorporation of Al3+ into the SBA-15 matrix generates weak acidic sites and the total acidity generated increases with decrease in the Si/Al mole ratio (i.e. increase in amount of Al3+ incorporated). The activity results showed that the hydrodeoxygenation of dibenzofuran proceeds via hydrogenation of the benzene rings on the Ni sites followed by cleavage of C-O bonds on the acidic sites of the catalyst to yield unsaturatedhydrocarbons. Further hydrogenation of unsaturated hydrocarbons on the Ni sites gives bicyclohexyl as the major product. A remarkable 100.00% dibenzofuran conversion was found for all the catalysts except for Ni/SBA-15 and Ni/Al-SBA-15 (80) (Si/Al mole ratio = 80) catalysts, which showed 97.97% and 99.31%, respectively. Among the synthesized catalysts, the Ni/Al-SBA-15(50) (Si/Al mole ratio = 50) catalyst showed the highest efficiency (due to its high acidity), with superior selectivity of ~87.00% for bicyclohexyl and ~96.00% degree of deoxygenation at 10 MPa, 260 °C and 5 h. The obtained activity results reveal the synergetic effect of Ni and support in the hydrodeoxygenation of dibenzofuran reaction: the concentration of acidic sites has a significant effect on the selectivity of the desired products Further, the activity of Ni/Al-SBA-15(50) (being the most effective catalyst) was investigated for hydrodeoxygenation of guaiacol in a batch reactor at 5 MPa. The activity results showed that the reaction proceeded via demethoxylation of guaiacol to produce phenol, followed by direct hydrogenolysis to produce benzene. Subsequent hydrogenation of the benzene produces cyclohexane. After 3 h of reaction at 250 oC, 89.00% conversion, 74.97% degree of deoxygenation and 60.40% cyclohexane selectivity were achieved.